PENGARUH KUALITAS PRODUK, CITRA MEREK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING PADA KONSUMEN DI KABUPATEN BOGOR - Mujito; Nur Khapifah; Benny Osta Nababan; Wawan Hari Subagyo (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2024)
This research aims to determine the influence of product quality, brand image, price, and promotion on purchasing decisions for Scarlett Whitening products among customers in Bogor Regency. This research uses quantitative methods and a type of causality research using data in the form of numbers and analyzed using statistical analysis, to determine the influence of variables (X), namely product quality, brand image, price and promotion on purchasing decisions for Scarlett Whitening products as variable (Y). The population of this study are consumer who have used at least on purchase of Scarlett Whitening products in Bogor Regency, with sample size of 100 respondents. The data collection technique was carried out using a questionnaire, while for data analysis using SPSS version 22 to test, namely the validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple analysis T test (Partial Test), and F test (Simultaneous test). The results of this research show that the variables product quality, brand image, price, and promotion simultaneously influence the decision to purchase Scarlett Whitening product. Meanwhile, in the T test, product quality has no influence on the decision to purchase Scarlett Whitenin product. Brand image, price, and promotion influence the decision to purchase Scarlett Whitening product.